An empirical study on the relationships between tqm practices and overall service performance: The case of a public service sector in Malaysia / Arawati Agus and Za’faran Hassan - Agus, Arawati; Hassan, Za’faran (Universiti Teknologi MARA Cawangan Pahang, 2006)
In recent years, the TQM movement has swept the service sector in Malaysia because the shift towards quality practices is crucial to the survival of service firms. Some studies have proven that TQM practices have significantly positive impact on organizational performances. This study sought to enhance understandings of relationships between TQM practices and the overall service performance of a public service sector in Malaysia. Methods include correlation and multiple regression analyses. The result of the overall multiple linear regression indicates that the model has a good fit. In addition, this paper further investigates correlations of the variables and the overall regression model for the present of multicollinearity and found that its existence is low. The overall result from the multiple linear regression suggests that some of the regression coefficients of the predictor variables (TQM practices) are significant toward explaining the dependent variable (service performance).